Adhesion and Adhesives Technology : An Introduction. - Pocius, Alphonsus V. (Hanser, 2021)
This book describes in clear understandable language the three main disciplines of adhesion technology: mechanics of the adhesive bond; chemistry of adhesives; and surface science. Some knowledge of physical and organic chemistry is assumed but no familiarity with the science of adhesion is required.
12.6.1 Attempts to Artificially Produce the Gecko Features and Adhesive Ability.
Keywords: Adhesion.; Adhesives.; elektronické knihy; electronic books